Critical Analysis of Nike and Nike's Marketing Strategies ---------------------From the US to China on Cultural Basis - Miao, Jinyan (2011)
Nike as the world biggest athletic brand, it has expanded abroad for many years. During its international business in the overseas markets, it drew many experiences from the initial failures. There are many different factors that influence Nike's expansion outside the US, and cultural differences are main of them. Therefore, a research was carried out to seek out how Nike made its marketing strategy based on cultural gaps between the US and China. Three main questions were asked to relevant staffs in Nike store. First, what are Nike's strengths, weaknesses and opportunities in international market? Second, what are the marketing strategies for Nike in China? Third, based on culture differences, are there any suggestions for Nike to launch new products which are special for China market? According to Nike's marketing strategy, several models of marketing across cultures are used, for example, Hofstede's model, Hall's model, 4Ps, 4Cs and so on. Besides, interview and field research are taken to find out Nike's marketing strategy in China market. Nike's marketing strategy is related to Nike's current situation, so it is necessary to make clear Nike's strengths, weakness, opportunities and challenges. After the analysis of Nike's marketing strategy both in the US and China, some useful suggestions to Nike in China are given out in the end.